Graphite negative electrode material and preparation method thereof, and secondary battery
By forming a composite structure of an amorphous carbon layer and a lithium phosphate layer on the surface of the graphite negative electrode material, the problems of long charging time of lithium-ion batteries and high cost of coating Li3PO4 are solved, and the fast charging and efficient electrochemical performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411850558.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lithium-ion batteries have been charged at room temperature for too long to meet the fast charging needs. The existing Li3PO4 coating method is costly, complex in process and unstable in structure.
Using graphite negative electrode material, the composite structure of an amorphous carbon layer and a lithium phosphate layer is formed on the surface of the graphite core, the process is simplified and the cost is reduced, ensuring the structural stability of the cladding layer.
It significantly improves the fast charging capacity of lithium-ion batteries, improves the first-time Coulomb efficiency and capacity retention rate, while reducing production costs and process complexity.
Smart Images

Figure CN119674004A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon material preparation, and in particular to a graphite negative electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] Graphite material is the most widely used negative electrode active material in lithium-ion batteries. It is widely used in electric vehicles, digital products and other fields due to its advantages such as high operating voltage, high energy density, low self-discharge rate, no memory effect, long cycle life and environmental friendliness.
[0003] With the popularity of electric vehicles, consumers' expectations for charging time are also increasing, hoping to shorten charging time and improve the convenience of electric vehicles. However, even if the positive and negative electrode materials and electrolytes have been optimized, typical lithium-ion batteries still take more than 30 minutes to fully charge at room temperature, which obviously cannot meet the market's growing demand for fast charging capabilities.
[0004] Among them, the key to improving the charging rate of lithium-ion batteries is how to promote the Li + Desolvation process. Studies have shown that the solid electrolyte membrane (SEI membrane) rich in Li3PO4 can weaken the Li + The interaction with the solvent accelerates the Li + The dissolution process. At present, the industry uses a solid electrolyte (SEI film) coated with Li3PO4 on the surface to modify graphite materials and improve the fast charging performance of graphite materials. The current atomic deposition method for coating lithium phosphate is extremely expensive and has very strict process requirements. Although there are also references to preparing Li3PO4-coated graphite materials using a lithium source and a phosphate source as precursors, this method has problems with uneven coating and unstable coating structure.
[0005] Therefore, it is particularly important to find a modification method for coating Li3PO4 on the graphite surface with simple operation process, low cost and stable structure. Summary of the invention
[0006] The purpose of the present invention is to provide a graphite negative electrode material and a preparation method thereof. The graphite negative electrode material can effectively promote the Li + The desolvation process greatly improves the fast charging capability of lithium-ion batteries. The preparation method is simple and can form a lithium phosphate layer with uniform coating and stable structure on the graphite surface.
[0007] To achieve the above objectives, the first aspect of the present invention provides a graphite negative electrode material, including a graphite core and a composite outer layer, wherein the composite outer layer includes an amorphous carbon layer and a lithium phosphate layer, and the amorphous carbon layer is between the graphite core and the lithium phosphate layer.
[0008] In the technical solution adopted by the present invention, the graphite negative electrode material includes a graphite core, an amorphous carbon layer and a lithium phosphate layer from the inside to the outside. The amorphous carbon layer in the middle can not only reduce the specific surface area of the graphite core and improve the initial coulomb efficiency of the graphite negative electrode material, but more importantly, the amorphous carbon layer can anchor the lithium phosphate in the outer layer to ensure the structural stability of the lithium phosphate layer as a coating layer. In addition, the lithium phosphate layer as an outer coating layer can weaken the Li + The interaction with the solvent accelerates the Li + The desolvation process is completed, thus greatly improving the fast charging performance of the graphite negative electrode material.
[0009] As a technical solution of the present invention, Dv50 is 10.0 to 12.0 μm.
[0010] As a technical solution of the present invention, the tap density is 0.90 to 1.10 g / cm 3 .
[0011] As a technical solution of the present invention, the specific surface area is 1.10 to 2.30 m 2 / g.
[0012] As a technical solution of the present invention, the reversible capacity at 0.1C is ≥350 mAh / g.
[0013] As a technical solution of the present invention, the 0.1C first coulombic efficiency is ≥90%.
[0014] As a technical solution of the present invention, the 3C / 0.2C capacity retention rate is ≥79.0%.
[0015] As a technical solution of the present invention, the thickness of the amorphous carbon layer is 20 to 500 nm.
[0016] As a technical solution of the present invention, the thickness of the lithium phosphate layer is 10 to 50 nm.
[0017] A second aspect of the present invention provides a method for preparing a graphite negative electrode material, comprising the steps of:
[0018] (I) mixing a graphite base material and a carbon coating agent to obtain a mixed material;
[0019] (II) carbonizing the mixture to obtain a precursor;
[0020] (III) mixing the precursor and lithium-containing powder and then subjecting them to heat treatment, wherein the lithium-containing powder contains a lithium source and a phosphoric acid source, and the lithium source and the phosphoric acid source undergo a dehydration reaction during the heat treatment.
[0021] The preparation method of the present invention first uses a carbon coating agent to carbonize the surface of a graphite base material to form an amorphous carbon layer before the lithium-containing powder is heat-treated, and then a lithium source and a phosphate source are dehydrated by heat treatment to generate lithium phosphate and uniformly deposited on the surface of the amorphous carbon layer. The amorphous carbon layer can anchor the outer lithium phosphate layer to avoid the lithium phosphate layer being directly deposited on the surface of the graphite base material and causing the coating layer to be unstable. In addition, the preparation method of the present invention is simple in process, easy to operate and low in cost. Only one carbonization treatment and one heat treatment are required to complete the coating process, which is conducive to application in industrial production.
[0022] As a technical solution of the present invention, the graphite base material includes at least one of artificial graphite, natural graphite and mesophase carbon microbeads.
[0023] As a technical solution of the present invention, the mass ratio of the graphite base material to the carbon coating agent is 95-98:2-5.
[0024] As a technical solution of the present invention, the mass ratio of the precursor to the lithium-containing powder is 90-98:2-10.
[0025] As a technical solution of the present invention, the carbonization treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of argon, nitrogen, helium and neon.
[0026] As a technical solution of the present invention, the heat treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of argon, nitrogen, helium and neon.
[0027] As a technical solution of the present invention, the temperature of the carbonization treatment is 900-1250° C., and the insulation time is 2-5 hours.
[0028] As a technical solution of the present invention, the temperature of the heat treatment is 400-800° C., and the insulation time is 2-8 hours.
[0029] As a technical solution of the present invention, the equipment used for mixing in step ① is a high-speed mixer.
[0030] As a technical solution of the present invention, the equipment used for mixing in step ③ is a high-speed mixer.
[0031] As a technical solution of the present invention, the carbon coating agent includes at least one of coal tar, asphalt and resin.
[0032] As a technical solution of the present invention, the coal tar includes at least one of high-temperature coal tar, medium-temperature coal tar and light oil, the asphalt includes at least one of petroleum asphalt, coal tar and natural asphalt, and the resin includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-meta-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide and polypropylene oxide.
[0033] As a technical solution of the present invention, the lithium source includes lithium hydroxide, and the phosphate source includes one or more of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and lithium dihydrogen phosphate.
[0034] As a technical solution of the present invention, the phosphoric acid source is lithium dihydrogen phosphate, and the molar ratio of the lithium hydroxide to the phosphate is 2:1.
[0035] As a technical solution of the present invention, the phosphate source is ammonium phosphate, diammonium phosphate or diammonium hydrogen phosphate, and the molar ratio of the lithium hydroxide to the phosphate is 3:1.
[0036] A third aspect of the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material comprises the aforementioned graphite negative electrode material, or a graphite negative electrode material prepared by the aforementioned method for preparing the graphite negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the structure of the graphite negative electrode material of the present invention.
[0038] Figure 2 This is the XRD spectrum of the graphite negative electrode material of Example 1.
[0039] Figure 3 This is the EDS image of the graphite negative electrode material of Example 1. DETAILED DESCRIPTION
[0040] The graphite negative electrode material of the present invention can be used alone or mixed with other negative electrode materials (such as natural graphite, soft carbon, hard carbon, silicon-carbon composite material, silicon-oxygen composite material, etc.). The graphite negative electrode material can be used in a secondary battery, which includes a positive electrode material, a negative electrode material and an electrolyte.
[0041] The positive electrode material may be a layered transition metal lithium oxide or an olivine-type lithium compound. The layered transition metal lithium oxide may be, but is not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (chemical formula LiNi x Co y Mn (1-x-y) M z O2, wherein 0.6≤x<0.9, x+y<1, 0≤z<0.08, M is at least one of Al, Mg, Zr and Ti) and coatings and dopants of the above materials. Olivine-type lithium compounds are lithium-containing phosphates with an olivine structure, which may be, but are not limited to, lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate and coatings and dopants of the above materials. These positive electrode active materials may be used alone or in combination of two or more. Of course, the positive electrode materials of the present invention are not limited to the positive electrode materials listed above, and other positive electrode materials that can be used for lithium ion deintercalation are also possible.
[0042] The electrolyte includes an electrolyte salt, a non-aqueous organic solvent and an additive. The electrolyte salt may be, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(oxalate)borate (C4BLiO8), lithium difluorooxalate borate (C2BF2LiO4), lithium difluorophosphate (LiPO2F2) and lithium difluorobis(oxalate)phosphate (LiDFBP). The non-aqueous organic solvent is selected from carbonates and / or carboxylates. Further, the non-aqueous organic solvent is selected from at least one of ethylene carbonate (PC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate. Additives may include ethylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfate (ES), propane sulfonate (PS), etc. Of course, the electrolyte of the present invention is not limited to the combination of the electrolyte salt, non-aqueous organic solvent and additive listed above, and other electrolytes that can shuttle lithium ions are also possible.
[0043] The graphite negative electrode material of the present invention can be used as an example. Figure 1As shown, the graphite negative electrode material 100 includes a graphite core 10 and a composite outer layer 30. The composite outer layer 30 includes an amorphous carbon layer 31 and a lithium phosphate layer 33, and the amorphous carbon layer 31 is between the graphite core 10 and the lithium phosphate layer 33. The amorphous carbon layer 31 acts as a bridge to improve the structural stability of the outer lithium phosphate layer 33. The thickness of the amorphous carbon layer is 20 to 500 nm, and as an example, it can be but not limited to 20 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm. The thickness of the lithium phosphate layer is 10 to 50 nm, and as an example, it can be but not limited to 10 nm, 20 nm, 30 nm, 40 nm, 50 nm.
[0044] The 0.1C reversible capacity of the graphite negative electrode material is ≥350mAh / g, as an example, it can be but not limited to ≥350mAh / g, ≥355mAh / g, ≥360mAh / g, ≥365mAh / g, ≥370mAh / g, ≥375mAh / g, ≥380mAh / g, ≥385mAh / g, ≥390mAh / g. The 0.1C first coulombic efficiency of the graphite negative electrode material is ≥90%, as an example, it can be but not limited to ≥90%, ≥91%, ≥92%, ≥93%, ≥94%, ≥95%. The 3C / 0.2C capacity retention rate of the graphite negative electrode material is ≥ 79.0%. As an example, it can be but not limited to 79.0%, 80.0%, 81.0%, 82.0%, 83.0%, 84.0%, 85.0%, 86.0%, 87.0%, 88.0%, 89.0%, 90.0%, 91.0%, 92.0%, 93.0%, 94.0%, and 95.0%.
[0045] The Dv50 of the graphite negative electrode material is 10.0-12.0 μm, for example, it can be but not limited to 10.0 μm, 10.2 μm, 10.4 μm, 10.6 μm, 10.8 μm, 11.0 μm, 11.2 μm, 11.4 μm, 11.6 μm, 11.8 μm, 12.0 μm. The tap density is 0.90-1.10 g / cm 3 , as an example, it can be but not limited to 0.90 g / cm 3 , 0.92g / cm 3 、0.94g / cm 3 , 0.96g / cm 3 、0.98g / cm 3 , 1.00g / cm 3 , 1.02g / cm 3 , 1.04g / cm 3 , 1.06g / cm 3, 1.08g / cm 3 , 1.10g / cm 3 Specific surface area is 1.10~2.30m 2 / g, as an example, it can be but not limited to 1.10m 2 / g, 1.20m 2 / g, 1.30m 2 / g, 1.40m 2 / g, 1.50m 2 / g, 1.60m 2 / g, 1.70m 2 / g, 1.80m 2 / g, 1.90m 2 / g, 2.00m 2 / g, 2.10m 2 / g, 2.20m 2 / g, 2.30m 2 / g.
[0046] The preparation method of the graphite negative electrode material of the present invention comprises the following steps: (I) mixing a graphite base material and a carbon coating agent to obtain a mixture; (II) carbonizing the mixture to obtain a precursor; and (III) mixing the precursor and a lithium-containing powder and then performing a heat treatment, wherein the lithium-containing powder contains a lithium source and a phosphoric acid source, and the lithium source and the phosphoric acid source undergo a dehydration reaction during the heat treatment.
[0047] Wherein, in step (I), the graphite base material includes at least one of artificial graphite, natural graphite and mesophase carbon microspheres. The carbon coating agent includes at least one of coal tar, asphalt and resin. Coal tar includes at least one of high temperature coal tar, medium temperature coal tar and light oil. Asphalt includes at least one of petroleum asphalt, coal asphalt and natural asphalt. Resin includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-m-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide and polypropylene oxide. The equipment used for mixing can be a high-speed mixer. The mass ratio of graphite base material and carbon coating agent is 95-98:2-5. As an example, the mass ratio can be but not limited to 95:2, 95:3, 95:4, 95:5, 96:2, 96:3, 96:4, 96:5, 97:2, 97:3, 97:4, 97:5, 98:2, 98:3, 98:4, 98:5.
[0048] In step (II), the carbonization treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of argon, nitrogen, helium and neon. The temperature of the carbonization treatment is 900-1250°C. As an example, the temperature can be, but not limited to, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C. The insulation time is 2-5h. As an example, the insulation time can be, but not limited to, 2h, 3h, 4h, 5h.
[0049] In step (III), the mass ratio of the precursor to the lithium-containing powder is 90-98:2-10. As an example, the mass ratio may be, but is not limited to, 90:2, 90:5, 90:7, 90:10, 96:2, 96:5, 96:7, 96:10, 97:2, 97:5, 97:7, 97:10, 98:2, 98:5, 98:7, 98:10. The lithium source includes lithium hydroxide, and the phosphate source includes one or more lithium dihydrogen phosphate and / or lithium dihydrogen phosphate of ammonium phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate. If the phosphate source is lithium dihydrogen phosphate, the molar ratio of lithium hydroxide to phosphate is 2:1. If the phosphate source is ammonium phosphate, diammonium hydrogen phosphate or diammonium hydrogen phosphate, the molar ratio of lithium hydroxide to phosphate is 3:1. The equipment used for mixing may be a high-speed mixer. The heat treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of argon, nitrogen, helium and neon. The temperature of the heat treatment is 400-800°C. As an example, the temperature can be, but is not limited to, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C. The insulation time is 2-8h. As an example, the insulation time can be, but is not limited to, 2h, 3h, 4h, 5h, 6h, 7h, 8h.
[0050] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0051] Example 1
[0052] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0053] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0054] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0055] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0056] The graphite negative electrode material prepared in Example 1 was subjected to XRD and EDS tests, and the results are as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the diffraction peaks are mainly 2H phase graphite (standard card 74-1160), indicating that the main material is graphite. The weak peaks at diffraction angles of 22°, 23° and 24° correspond to the Li3PO4 phase (standard card 15-0760), indicating the presence of Li3PO4 phase in the coating layer. The lower diffraction peak intensity is related to the lower Li3PO4 content. Figure 3 It can be seen that the elements C / P / O are evenly dispersed on the surface of the material, indicating that the Li3PO4 fast ion conductor can be evenly formed in the graphite negative electrode material, further proving that Li3PO4 can be successfully introduced.
[0057] Example 2
[0058] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0059] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0060] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0061] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 98:2 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0062] Example 3
[0063] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0064] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0065] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0066] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 600° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0067] Example 4
[0068] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0069] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0070] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0071] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 600° C. and the heat preservation time was 2 hours to obtain a graphite negative electrode material.
[0072] Example 5
[0073] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0074] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0075] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0076] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 98:2 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 600° C. and the heat preservation time was 2 hours to obtain a graphite negative electrode material.
[0077] Example 6
[0078] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0079] (I) In a dry environment, artificial graphite and phenolic resin are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0080] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0081] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0082] Example 7
[0083] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0084] (I) In a dry environment, natural graphite and petroleum asphalt are weighed in a mass ratio of 96:4 and placed in a high-speed mixer to mix to obtain a mixture.
[0085] (II) The mixed material is placed in an argon atmosphere for high-temperature carbonization treatment at a temperature of 1000° C. and kept at this temperature for 4 hours to obtain a precursor.
[0086] (III) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0087] Example 8
[0088] This embodiment is a method for preparing a graphite negative electrode material, which includes the following steps.
[0089] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0090] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. and kept at this temperature for 5 hours to obtain a precursor.
[0091] (III) LiOH and (NH4)2HPO4 were weighed in a molar ratio of 3:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0092] Comparative Example 1
[0093] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.
[0094] (I) In a dry environment, artificial graphite and petroleum asphalt are weighed in a mass ratio of 95:5 and placed in a high-speed mixer to mix to obtain a mixture.
[0095] (II) The mixed material is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. for 5 hours to obtain a graphite negative electrode material.
[0096] Comparative Example 2
[0097] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.
[0098] LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. Artificial graphite and lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800°C and the holding time was 5 hours to obtain a graphite negative electrode material.
[0099] Comparative Example 3
[0100] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.
[0101] (I) placing artificial graphite in a vapor deposition chamber, introducing argon at a rate of 800 sccm, and heating the artificial graphite to 1000° C. at a rate of 15° C. / min in an argon atmosphere. Passing methane into the vapor deposition chamber, and passing hydrogen into the vapor deposition chamber, wherein the amount of carbon-containing gas introduced is 100 sccm and the amount of hydrogen introduced is 150 sccm, and after ventilating for 30 minutes, a precursor of graphene-coated graphite is obtained.
[0102] (II) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder. The precursor and the lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a graphite negative electrode material.
[0103] Comparative Example 4
[0104] This comparative example is a method for preparing a graphite negative electrode material, which includes the following steps.
[0105] (I) LiOH and LiH2PO4 were weighed in a molar ratio of 2:1 and mixed in a high-speed mixer to obtain lithium-containing powder, artificial graphite and lithium-containing powder were weighed in a mass ratio of 95:5 and mixed in a high-speed mixer and then placed in a nitrogen atmosphere for heat treatment. The heat treatment temperature was 800° C. and the heat preservation time was 5 hours to obtain a precursor.
[0106] (II) In a dry environment, a precursor and petroleum asphalt are weighed in a mass ratio of 95:5 and mixed in a high-speed mixer to obtain a mixture.
[0107] (III) The mixture is placed in a nitrogen atmosphere for high-temperature carbonization treatment at a temperature of 1150° C. for 5 hours to obtain a graphite negative electrode material.
[0108] The graphite negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to various performance tests. The test conditions are as follows. The test results are shown in Table 1.
[0109] Malvern laser particle size analyzer MS2000 was used for particle size test. Dandong Better BT-302 tap density instrument was used to test the tap density of graphite negative electrode material. Micrometer 3020 was used to test the specific surface area of graphite negative electrode material.
[0110] The electrical performance of the graphite negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4 was tested by a half-cell test method. The test method is: the graphite negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4, the N-methylpyrrolidone solution of polyvinylidene fluoride with a concentration of 6wt.%, and SP were mixed in a mass ratio of 92:4:4 and evenly coated on a copper foil, and then placed in a vacuum drying process at 105°C for 24h to obtain a pole piece. Then it was transferred to an argon-filled glove box to be assembled into a button cell, with a three-component mixed solvent of 1mol / L LiPF6 in a DMC:EC:EMC=1:1:1 (volume ratio) mixed solution as the electrolyte, a metal lithium sheet as the counter electrode, and a 16μm thick U-shaped diaphragm as the isolation membrane. The assembled half-cell was tested for electrochemical performance on an electrochemical detection system. At room temperature, discharge at a constant current of 0.1C until the voltage reaches 0.01V, then discharge at a constant current of 0.02C until the voltage reaches 0.005V, and charge at a constant current of 0.1C until the voltage reaches 1.5V. The capacity charged to 1.5V is the 0.1C first charge capacity, and the ratio of the first charge capacity to the first discharge capacity is the first coulomb efficiency. After 1 week of 0.1C charging and 0.2C discharging cycles, constant current and constant voltage charging is performed at a rate of 3.0C (cutoff condition is 0.01C), followed by 3.0C constant current discharge, and the reversible capacity at 3.0C rate is recorded and compared with the reversible capacity at 0.2C to obtain the 3.0C / 0.2C capacity retention rate.
[0111] Table 1 Performance test results of graphite negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 4
[0112]
[0113]
[0114] From the results in Table 1, it can be seen that compared with comparative examples 1 to 4, the 3C / 0.2C capacity retention rates of embodiments 1 to 8 are all improved, and the introduction of the lithium phosphate layer into the outer layer does not affect the basic properties of graphite (such as particle size, tap density, specific surface area and capacity). It can be seen that the present invention sequentially arranges an amorphous carbon layer and a lithium phosphate layer on the surface of the graphite core, which can reduce the Li + The interaction with the solvent accelerates the Li + The desolvation process can greatly improve the fast charging performance of graphite negative electrode materials.
[0115] In Comparative Example 2, due to the lack of amorphous carbon coating, its Dv50 is too small, the specific surface area is too large, and there are many side reactions, which leads to a decrease in the first coulombic efficiency. At the same time, due to the lack of amorphous carbon coating, the structural stability of the lithium phosphate layer is not good, and its rate performance is not good. In Comparative Example 3, the middle layer is not an amorphous carbon layer, but a crystalline graphene layer, which cannot achieve the anchoring effect of the amorphous carbon layer. The lithium phosphate structure of the outer layer is unstable, so the rate performance is not good. In Comparative Example 4, the order of the amorphous carbon layer and the lithium phosphate layer is swapped, which cannot fundamentally change the phenomenon of the unstable structure of the lithium phosphate layer. In addition, the lithium phosphate layer as an intermediate layer also affects and cannot directly contact the electrolyte, thereby promoting Li + The desolvation process leads to poor rate performance.
[0116] By comparing Example 1 with Example 6, it can be seen that the graphite negative electrode material made of a hard carbon-type carbon coating agent of resin has a larger interlayer spacing than the graphite negative electrode material made of a soft carbon-type carbon coating agent of asphalt, so the 3C / 0.2C capacity retention rate is better, but other basic performance indicators are slightly reduced. By comparing Example 1 with Example 7, it can be seen that the graphite negative electrode material made of natural graphite as the core has a high gram capacity, but because its degree of graphitization is higher than that of artificial graphite, its rate performance is poor.
[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A graphite negative electrode material, characterized in that: The invention comprises a graphite inner core and a composite outer layer, wherein the composite outer layer comprises an amorphous carbon layer and a lithium phosphate layer, and the amorphous carbon layer is located between the graphite inner core and the lithium phosphate layer.
2. The graphite negative electrode material according to claim 1, characterized in that Includes at least one of the following features ① to ⑧: ①Dv50 is 10.0~12.0μm; ②Tap density is 0.90~1.10g / cm 3 ; ③Specific surface area is 1.10~2.30m 2 / g; ④0.1C reversible capacity ≥350mAh / g; ⑤0.1C first coulombic efficiency ≥ 90%; ⑥3C / 0.2C capacity retention rate ≥ 79.0%; ⑦ The thickness of the amorphous carbon layer is 20 to 500 nm; ⑧The thickness of the lithium phosphate layer is 10 to 50 nm.
3. A method for preparing a graphite negative electrode material, characterized in that: Includes steps: (I) mixing a graphite base material and a carbon coating agent to obtain a mixed material; (II) carbonizing the mixture to obtain a precursor; (III) mixing the precursor and lithium-containing powder and then subjecting them to heat treatment, wherein the lithium-containing powder contains a lithium source and a phosphoric acid source, and the lithium source and the phosphoric acid source undergo a dehydration reaction during the heat treatment.
4. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The invention comprises at least one of the following features (1) to (9): (1) The graphite base material comprises at least one of artificial graphite, natural graphite and mesophase carbon microspheres; (2) The mass ratio of the graphite base material to the carbon coating agent is 95-98:2-5; (3) The mass ratio of the precursor to the lithium-containing powder is 90-98:2-10; (4) The carbonization treatment is carried out under a protective atmosphere, wherein the protective atmosphere comprises at least one of argon, nitrogen, helium and neon; (5) The heat treatment is carried out under a protective atmosphere, wherein the protective atmosphere comprises at least one of argon, nitrogen, helium and neon; (6) The temperature of the carbonization treatment is 900-1250° C., and the holding time is 2-5 hours; (7) The heat treatment temperature is 400 to 800° C. and the holding time is 2 to 8 hours; (8) The mixing equipment used in step ① is a high-speed mixer; (9) The mixing device used in step ③ is a high-speed mixer.
5. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The carbon coating agent includes at least one of coal tar, pitch and resin.
6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: The coal tar includes at least one of high-temperature coal tar, medium-temperature coal tar and light oil, the asphalt includes at least one of petroleum asphalt, coal asphalt and natural asphalt, and the resin includes at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-meta-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide and polypropylene oxide.
7. The method for preparing a graphite negative electrode material according to claim 3, characterized in that: The lithium source includes lithium hydroxide, and the phosphate source includes one or more of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and lithium dihydrogen phosphate.
8. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: The phosphoric acid source is lithium dihydrogen phosphate, and the molar ratio of the lithium hydroxide to the phosphate is 2:
1.
9. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: The phosphoric acid source is ammonium phosphate, ammonium dihydrogen phosphate or diammonium hydrogen phosphate, and the molar ratio of the lithium hydroxide to the phosphate is 3:
1.
10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material comprises the graphite negative electrode material according to claim 1 or 2, or the graphite negative electrode material prepared by the method for preparing the graphite negative electrode material according to any one of claims 3 to 9.